2018
DOI: 10.1029/2017jd027907
|View full text |Cite
|
Sign up to set email alerts
|

Revisited Asian Monsoon Hydroclimate Response to Volcanic Eruptions

Abstract: A multiproxy study of the climatic impact after the 1815 Tambora eruption in China found substantial discrepancies among the historical documents, proxy reconstructions, and model simulations.To understand whether the discrepancies are associated with regional-scale heterogeneous hydroclimate responses or the specialty of an individual volcanic event, we revisit the Asian monsoon hydroclimate response to volcanic eruptions over the past five centuries using an independent warm season precipitation reconstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…In the southern Asian monsoon region, spatial patterns of the MMEMs in Years 0 and 1 agree well with precipitation anomaly pattern after Krakatau and Pinatubo eruptions shown in Zambri and Robock (2016). The identified wet areas in the EASM are close to that in Gao and Gao (2018), which showed an increased precipitation over the Yangtze-Huaihe River valley using Feng et al (2013) precipitation reconstruction. The patterns are also consistent with the observed precipitation and the PDSI variations shown in Trenberth and Dai (2007), with a drying effect in the SASM, the SeA and the northern EASM, and wetting effect in the w-SA and the southern EASM after the Mount Pinatubo eruption.…”
Section: 1029/2020jd032831supporting
confidence: 71%
“…In the southern Asian monsoon region, spatial patterns of the MMEMs in Years 0 and 1 agree well with precipitation anomaly pattern after Krakatau and Pinatubo eruptions shown in Zambri and Robock (2016). The identified wet areas in the EASM are close to that in Gao and Gao (2018), which showed an increased precipitation over the Yangtze-Huaihe River valley using Feng et al (2013) precipitation reconstruction. The patterns are also consistent with the observed precipitation and the PDSI variations shown in Trenberth and Dai (2007), with a drying effect in the SASM, the SeA and the northern EASM, and wetting effect in the w-SA and the southern EASM after the Mount Pinatubo eruption.…”
Section: 1029/2020jd032831supporting
confidence: 71%
“…Over Asia, the JJA hydroclimatic response to volcanic eruptions has been analyzed previously, based on both tree-ring data ( 24 , 25 ) and the CESM-LME ( 9 , 13 ), with diverging results. Our results indicate wetter conditions following eruptions over southern continental Asia alongside a drier climate over Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…The largest TVEs of the twentieth century (Agung 1963, El Chichón 1982, and Mount Pinatubo 1991) coincided with prevailing El Niño conditions ( 64 ). Some studies analyzing the impacts of volcanic events on climate have thus suggested the need to remove the ENSO signal prior to the analysis by either detrending the data ( 19 ) or considering the residuals after regressing the data against ENSO ( 25 ). Here, we did not remove the ENSO signal from the variables studied, as the median ensemble value of the PHYDA Niño 3.4 index in the year preceding each selected eruption was close to zero and thus indicates that neutral conditions were the dominant ENSO state prior to the analyzed eruptions ( SI Appendix , Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cook et al, ); though inferences of rainfall responses are indirect, and associated uncertainties can be large (Anchukaitis et al, ). Attempts to evaluate climate models with these records are complicated by uncertainties in the aerosol distributions (Crowley et al, ; Crowley & Unterman, ; Gao et al, ; Gao & Gao, ; Mann et al, ; Sigl et al, ). This is particularly important with regard to the seasonal and latitudinal details of volcanic aerosol forcing, as the months and locations of many eruptions of the LM are poorly known.…”
Section: Introductionmentioning
confidence: 99%